Legal Study of Null Verdicts in the Context of Narcotics - Abdul Azis Mustofa; Endang Sutrisno (International Journal of Social Service and Research, 2026)
A court verdict is a statement issued by a judge in an open hearing, which is a guilty verdict, acquittal, acquittal, legal pardon, or an order to commit certain actions. These types of decisions or verdicts are regulated in Articles 65 and 66 of the 2023 Criminal Code. A null verdict or verdict is not explicitly contained in any law, so it is questionable about its legal certainty. This study aims to analyze judges' considerations in null verdicts to achieve legal certainty and analyze null verdicts based on the 2023 Criminal Code. The method applied was normative juridical by utilizing primary and secondary data as well as legal material triangulation validation techniques. The results of this study are that the decision is null and void starting from the judge's interpretation in interpreting article 67 of the Criminal Code, which if in the 2023 Criminal Code is in article 129. However, legal reform and harmonization need to be carried out to build more substantive legal certainty because it will have implications for legal systematics.